Transport Corridors in Africa. - Lamarque, Hugh. (Boydell & Brewer, Limited, 2022)
In-depth examination of the inherent tensions and dynamics of transport corridors in Africa: between short-term optics and long-term durability; between regional integration and national interest; between the facilitation of trade and the generation of corridor revenue.